IL-9 Modulated MUC4 Gene and Glycoprotein Expression in Airway Epithelial Cells. Issue 1 (15th June 2006) - Damera, Gautam; Xia, Baoyun; Ancha, Hanumatha R.; Sachdev, Goverdhan P.
Abstract : Compromised epithelial cell integrity is a common feature associated with chronic lung inflammatory states such as asthma. While epithelial cell damage is largely due to sustained effects of inflammatory mediators localized to airways, the subsequent process of epithelial cell differentiation is attributed to members of the transmembrane receptor tyrosine kinase family called the ErbB's. MUC4, a large molecular weight membrane-bound glycoprotein, has recently been identified as a potential ligand for the ErbB-2 receptor. In this study, we investigated the possible role of interleukin-9 (IL-9), a Th2 cytokine, on MUC4 expression using a lung cancer cell line, NCI-H650. We determined that IL-9 up-regulates MUC4 expression in a time and concentration-dependent fashion. Nuclear run-on assays indicated transcriptional regulation of MUC4 while no post-transcriptional mRNA stabilization was observed by actinomycin D chase experiments. IL-9 also increased MUC4 glycoprotein expression as determined by Western blots using a monoclonal antibody specific for a non-tandem repeat region on ASGP-2 region of MUC4. Furthermore, a JAK3-selective inhibitor 4-(4′-hydroxyphenyl) amino-6, 7-dimethoxyquinazoline (WHI-P131), substantially reduced IL-9-induced MUC4 mRNA expression in a dose-dependent fashion. These results implicate a potential role for IL-9 upon MUC4 expression in human airway epithelial cells.